Effect of experimental jaw muscle pain on EMG activity and bite force distribution at different level of clenching. (31st August 2013) - Shimada, A.; Hara, S.; Svensson, P.
Summary: Bite force at different levels of clenching and the corresponding electromyographic (EMG) activity in jaw‐closing muscles were recorded in 16 healthy women before, during and after painful stimulation of the left masseter muscle. Experimental pain was induced by infusion of 5·8% hypertonic saline (HS), and 0·9% isotonic saline (IS) was infused as a control. EMG activity was recorded bilaterally from the masseter and temporalis muscles, and static bite force was assessed by pressure‐sensitive films (Dental Pre‐scale) at 5, 50 and 100% of maximal voluntary contraction (MVC) during each session. Visual feedback was applied by showing EMG activity to help the subject perform clenching at 5, 50 and 100% MVC, respectively. EMG activity at 100% MVC in left and right masseter decreased significantly during painful HS infusion (1·7–44·6%; P < 0·05). EMG activity at 5% and 50% MVC was decreased during HS infusion in the painful masseter muscle (4·8–18·6%; P < 0·05); however, EMG activity in the other muscles increased significantly (18·5–128·3%; P < 0·05). There was a significant increase in bite force in the molar regions at 50% MVC during HS infusion and in the post‐infusion condition ( P < 0·05). However, there were no significant differences in the distribution of forces at 100% MVC. In conclusion, experimental pain in the masseter muscle has an inhibitory effect on jaw muscle activity at maximal voluntary contraction, and compensatory mechanisms may influence the recruitment pattern at submaximal efforts.